NOM removal by ultrafiltration membranes : enhancement of filtration performance - Wei, Xi (2008)
Raw water supplies in Singapore tend to contain high levels of natural organic matter (NOM) and other contaminants. The effective removal of NOM from surface water is a great challenge to the water industry. This work aims to study novel techniques to improve NOM filtration performance of UF membranes with low fouling tendency and high permeability through various approaches, not only from an engineering perspective, but also from the view of UF membrane characteristics. In order to achieve this target, as the first step, a comprehensive literature review has been conducted which focuses on the nature of NOM and its influence on the water, water treatment and membrane process especially membrane fouling. Since detailed characterizations are necessary due to the variation of NOM from different sources, the relevant characterization techniques were described. In addition, ultrafiltration membrane technology for NOM removal has been reviewed and a general description of NOM fouling has also been presented.